Epithelial to mesenchymal transition is increased in patients with COPD and induced by cigarette smoke. Issue 5 (7th January 2013) - Milara, Javier; Peiró, Teresa; Serrano, Adela; Cortijo, Julio
Abstract : Background: Cigarette smoking contributes to lung remodelling in chronic obstructive pulmonary disease (COPD). As part of remodelling, peribronchiolar fibrosis is observed in the small airways of patients with COPD and contributes to airway obstruction. Epithelial to mesenchymal transition (EMT) appears to be involved in the formation of peribronchiolar fibrosis. This study examines the EMT process in human bronchial epithelial cells (HBECs) from non-smokers, smokers and patients with COPD as well as the in vitro effect of cigarette smoke extract (CSE) on EMT. Methods: HBECs from non-smokers (n=5), smokers (n=12) and patients with COPD (n=15) were collected to measure the mesenchymal markers α-smooth muscle actin, vimentin and collagen type I and the epithelial markers E-cadherin, ZO-1 and cytokeratin 5 and 18 by real time-PCR and protein array. In vitro differentiated bronchial epithelial cells were stimulated with CSE. Results: Mesenchymal markers were upregulated in HBECs of smokers and patients with COPD compared with non-smokers. In contrast, epithelial cell markers were downregulated. In vitro differentiated HBECs underwent EMT after 72 h of CSE exposure through the activation of intracellular reactive oxygen species, the release and autocrine action of transforming growth factor β1, the phosphorylation of ERK1/2 and Smad3 and by the downregulation of cyclic monophosphate. Conclusions: The EMT process is present in bronchial epithelial cells of the small bronchi of smokers and patients with COPD and is activated by cigarette smoke in vitro.